Exploring the motivational states of English learning among Chinese EFL learners at tertiary-level: A perspective of Directed Motivational Currents - He, Xiang; Zhou, Dandan; Wu, Chang (Frontiers in Psychology, 2022)
Under the framework of Directed Motivational Currents (DMCs), the present study aimed to explore the motivational dynamics of Chinese Tertiary EFL learners English learning and identify the factors that affect Chinese EFL learners’ DMC-induced motivational states in their English learning process. With a longitudinal research design, the study collected data from ten focal Chinese EFL learners through trajectory equivalent modeling, reflective journal and semi-structured interview in a two-semester-long IELTS training course during the COVID-19 pandemic period. The collected data were processed by using qualitative content analysis and thematic analysis. The results indicated that: (1) Chinese EFL learners experienced the clear DMC-typed motivational surges during the process of English learning; (2) Chinese EFL learners’ DMC states were affected by various contextual factors, including important others, instructional climate as well as the exam pressure. The findings not only validate the structure of DMC in Chinese EFL context, but also offer pedagogical implications about how to facilitate the DMC-type motivation in language teaching.